Photovoltaic Modules for Indoor Energy Harvesting - Zekri, Wafaa Abd El-Basit (JOURNAL OF ADVANCES IN PHYSICS, 2018)
This paper presents the performance of indoor energy harvesting systems based on different photovoltaic modules (monocrystalline silicon, polycrystalline silicon, amorphous silicon and polymer) and artificial electric lighting sources (incandescent, fluorescent and cool white flood LED). In this concern, it is clearly proved that, maximum output power densities to be harvested from the photovoltaic module depends mainly on the spectral responses of both the light source and the module material. Herein, and from the study, experimental work, results and analysis, it is clear that monocrystalline silicon is the optimum solution for all light sources, followed by polycrystalline, whenever used with spot-and incandescent - lamps. On the other hand, amorphous samples were proved to be lightly sensitive to fluorescent light and cool white flood LED. Finally, polymer samples were weakly responded whenever exposed to any of the investigated light sources.